Safety and efficacy of Transurethral Bipolar Enucleation of prostate (TUBE) in BPH - Reddy Nalubolu, Mallikarjuna; Reddy Pogula, Vedamurthy; Reddy Challa, Sivasankar; reddy Gouru, Vijayabhaskar; byram, Ranadheer; Bodduluri, Sudeep; Maddiboina, Harikrishna (International Journal of Medical Research and Review, 2018)
Objectives: To evaluate the safety and efficacy of transurethral bipolar enucleation of the prostate due to benign prostatic hyperplasia. Methods: This is a prospective study and 37 patients undergoing Transurethral bipolar enucleation of the prostate (TUBE) for BPH will be taken for the study. Preoperative factors evaluated included International Prostate Symptom Score (IPSS), postvoid residual volume (PVR), estimated blood loss, operative time, pathologic weight, and complications. Postoperative evaluation was performed at 1month, 6 months and 12months. Results: Preoperative, 1 month, 6 months, and 12 months mean postvoid residual volumes were 235 mL, 33.6 mL, 20 mL and 20 mL; mean IPSS were 31.6, 2.97, 2.97 and 2.97; mean Q max was 5.8ml/sec, 20.23ml/sec,25.5ml/sec, and 25.5ml/sec; preoperative and post operative mean quality of life scores were 5.4 and 2.2; mean operative time was 87.5 minutes. Hemoglobin drop was 0.6g/dl, and pathologic weight was 45.45 g. 10 patients underwent partial enucleation. Early stress incontinence occurred in 9 patients (24.3%).Urinary tract infection occurred in 1 patient, and Superficial mucosal bladder injury in 1 patient. Conclusions: International Prostate Symptom Score, quality of life, Qmax, and postvoid residual volume (PVR) showed statistically significant improvements from baseline. TUBE is a safe, effective, and reproducible procedure for BPH.